Book review: Islam, liberalism, and ontology: a critical re-evaluation - El-Muhammady, Ahmad (IIUM Press, 2021)
In responding to the long-drawn debate between Islam and liberalism, Joseph J. Kaminski’s Islam, Liberalism, and Ontology: A Critical Re-evaluation offers two things: first, a critical analysis of the basic categories and constructs that comprise “Islam” and “liberalism” via a clearly defined methodological mode of inquiry; and second, plausible solution to the fundamental clashes between Islam and liberalism. What makes this book even more interesting, instead of taking a “scratch on the surface” approach with a spattering of references and anecdotes, the author dissected Islam and liberalism using ontological inquiry based on the primary and canonical sources. By doing so, he was hopeful that it ultimately serves as a useful asset and contribution for those studying comparative political theory or the relationship between international politics and religion.